A randomized placebo-controlled trial of using B vitamins to prevent cognitive decline in older mild cognitive impairment patients. Issue 8 (August 2020) - Kwok, Timothy; Wu, Yuanyuan; Lee, Jenny; Lee, Ruby; Yung, Cho Yiu; Choi, Grace; Lee, Vivian; Harrison, John; Lam, Linda; Mok, Vincent
Summary: Background & aims: Mild cognitive impairment (MCI) patients are at risk of cognitive decline, while elevated serum homocysteine is also associated with cognitive impairment. Thus, older people with MCI and hyperhomocysteinemia may be under greater risk of cognitive decline. We therefore performed a randomized trial of homocysteine-lowering by B vitamins supplementation to prevent cognitive decline in older MCI patients with elevated serum homocysteine. Methods: 279 MCI outpatients aged ≥65 years with serum homocysteine ≥10.0 μmol/L were randomly assigned to take either methylcobalamin 500 μg and folic acid 400 μg once daily, or two placebo tablets for 24 months. All subjects were followed up at 12 monthly intervals. The primary outcome was cognitive decline as defined by an increase in clinical dementia rating scale (CDR) sum of boxes (CDR_SOB). The secondary outcomes were global CDR, memory Z score, executive function Z score and Hamilton depression rating scale (HDRS) score. Results: The clinical characteristics between two groups were well matched, except that the supplement group had better executive function. The supplement effectively lowered serum homocysteine (mean 13.9 ± sd 3.5 μmol at baseline to 9.3 ± 2.4 μmol/L at month 24). At month 24, there was no significant group difference in CDR_SOB or any secondary outcomes (mean changes in CDR_SOB 0.36 versus 0.22 in supplement and placebo groups respectively). At month 12, the supplement group significantly improved in executive function and had lower HDRS score (P = 0.004 and 0.012 respectively). Group difference was significant for HDRS, but borderline significant for executive function. (P = 0.01; 0.06 respectively) These effects were not significant at month 24. Subgroup analysis showed that aspirin use had significant interaction with B supplements in CDR_SOB at month 24 (Beta 0.189, P = 0.005). Conclusions: Vitamin B12 and folic acid supplementation did not reduce cognitive decline in older people with MCI and elevated serum homocysteine, though the cognitive decline over two years in placebo group was small. The supplement led to a significant reduction in depressive symptoms at month 12, though this effect was not sustained. Aspirin use had a negative interaction effect on cognitive functioning with B supplements. Clinical trial registration: Centre for Clinical Research and Biostatistics (CCRB) Clinical Trials Registry: CUHK_CCT00373.